2017
DOI: 10.20396/bjos.v15i2.8648768
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different surface treatments of fiberglass posts on the bond strength to dentin

Abstract: Aim: To assess the influence of different fiberglass post surface treatments on the bond strength (BS) to root dentin. Methods: Thirty bovine root canals were endodontically treated and filled with gutta-percha and AH Plus sealer. At 24 h after the endodontic filling, the post spaces were prepared with Gates-Glidden drills and #3 drills of the DC White Post system, maintaining a 4 mm apical seal. The roots were randomly divided into three groups: S (fiberglass posts treated with silane), SA (fiberglass posts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Its application is effortless and easy, making it a widely accepted pre-treatment procedure among researchers. However, the effect on bond strength to dentine is unconvincing [22,[25][26][27][28]33,40], which might be due to the manual application of silane on the post surface and formed a non-homogenous layer, subsequently led to a weak chemical bond between silane and post [25]. Another reason could be the composition of the resin matrix of FRC posts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its application is effortless and easy, making it a widely accepted pre-treatment procedure among researchers. However, the effect on bond strength to dentine is unconvincing [22,[25][26][27][28]33,40], which might be due to the manual application of silane on the post surface and formed a non-homogenous layer, subsequently led to a weak chemical bond between silane and post [25]. Another reason could be the composition of the resin matrix of FRC posts.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be the composition of the resin matrix of FRC posts. It is reported that the methacrylate matrix bonds better to silane solution than epoxy resin containing FRC as depicted in Table 3 [21,22,25,29,40]. The interface between resin cement and post was also considered as a contributing factor for mechanical strength, where limited mechanical interlocking was mentioned between resin cement and untreated post surface [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In this case (mFRC at coronal third), during the push-out test, the applied force produces micro-fissures which are limited probably in the cement-micro-post area and do not reach the cement-dentin interface. For these reasons discussed above, the strength stress of the sFRC group was higher than the mFRC group at the coronal third, which indicates that there may be a good interaction of the resin cement with the post fiber [ 39 ]. In contrast, at the middle third, the anatomy shape of the root canal is conduct to have a low distribution of micro-post at the middle third compared to the coronal third.…”
Section: Discussionmentioning
confidence: 99%
“…This was an advantage shown in this work. According to Rechia et al [ 29 ], when silane is used in isolation, it can form a nonhomogeneous layer on the surface of the pins. The second explanation is that the brand of GFP may influence the BS, as some posts have more exposed fibers on their surfaces compared with others, which are more superficially protected by the epoxy resin matrix [ 2 , 22 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%